Affective and sexual relationships between women in prison (Revista Contexto & Educação, 2026)
Affective–sexual relationships among incarcerated women constitute experiences shaped by gender inequalities, institutional control, and the weakening of social bonds. This study aimed to analyze the factors that influence affective–sexual relationships among incarcerated women, considering the institutional context, power relations, and social markers that permeate these experiences. This is a field study with a qualitative approach, conducted in a female prison in the municipality of Salvador, Bahia, Brazil. Data production was carried out through semi-structured interviews with 13 incarcerated women participating in socio-educational workshops, and the analysis was conducted using content analysis. Four analytical categories emerged: family abandonment and partnership; need; safety; and physical attraction. The results indicate that affective–sexual relationships in prison are configured as strategies for coping with incarceration, associated with emotional deprivation, the search for protection, and the reconstruction of affective bonds in the face of family abandonment and institutional control. It was also observed that physical attraction is articulated through performative expressions of gender, especially the valorization of masculinized performances, understood as socially situated constructions rather than natural or pathological dispositions. It is concluded that the experience of sexuality in the female prison context is relational, dynamic, and socially constructed, and is traversed by interseccional markers of gender, race, class, and sexuality, highlighting the need for institutional policies and practices that recognize sexual rights and the complexity of the affective experiences of incarcerated women.
Keywords: women; arrests; sexuality; gender; social relationships